HUBUNGAN PENERAPAN PERATURAN MAHKAMAH AGUNG REPUBLIK INDONESIA NOMOR 2 TAHUN 2012 DENGAN KEADILAN BAGI TERDAKWA (KAJIAN TERHADAP PUTUSAN PENGADILAN MENGENAI PERKARA PENCURIAN RINGAN) - Baried, Rizky Ramadhan (Jurnal Yuridis, 2017)
Regulation of Indonesian Supreme Court Number 2 years 2012 has an interesting dynamic application, in first of two years after applied, court still view it as a regulation in socialiszation period, with the result that unsuccessful applied. Since in 2014, it started to be applied, even it started by police investigation, until based on authority from prosecutor, investigator can bestow light stealing case to court by way of rapid judicial procedure. By thus defendant?s right, that is gain a rapid judicial procedure, simple, and cheap has ful fill based on juridical practice.